The necessary construction of a paritary democracy for Private Law: gender equality in the management boards of listed companies - Martín Guardado, Sergio (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract.The paper that is presented tries to find arguments in favor of the possibility of extending the paritary democracy, a concept that emerged from Public Law, to the social and economic field. Only material equal equality between women and men can overcome the violation of human rights to which they are submitting to the majority of the population and, thus, consider the maximum use of the knowledge and skills of society. Then, the idea is to overcome female underrepresentation in the boards of directors of listed companies, linking their role and their performance in the markets in relation to decision-making in political power, more and more directly or indirectly submitted To the power of the markets. The development of the Social and Democratic State of Law, beyond the public, can materialize effective equality between women and men, adopting a concrete measure of positive action: quota system. In short, a constitutional justification for the necessary adoption of these policies is presented, formulating a paritary democracy for Private Law and a normative revision as a lege ferenda. Keywords: paritary democracy, listed companies, material equality, quotes, management boards.